Genetic parameters estimation in groups of Conilon coffee clones - Rodrigues, Wagner Nunes; Tomaz, Marcelo Antonio; Ferrão, Romário Gava; Ferrão, Maria Amélia Gava; Fonseca, Aymbiré Francisco Almeida da; Miranda, Fábio Demolinari de (Coffee Science - ISSN 1984-3909, 2012)
The cultivation of Coffea canephora var. kouilouensis De Wild (Conilon) is of great importance in Espírito Santo andtheir populations often have significant genetic variability. This study was aimed to evaluate three genotype groups of Conilon coffee,distinguished according to their maturation cycles, to estimate genetic parameters of different characteristics in order to betterunderstand their genetic structure. Estimates of genetic parameters were obtained from three experiments arranged according to thestatistical design in random blocks with four repetitions and five plants per plot. Individual and joint variance analyses were made toestimate genetic parameters and infer about the genetic variability of six agronomic traits: maturity cycle, productivity, visualassessment index, vigor, plant size and fruit size. The results indicate that the groups of clones showed high productivity and highgenetic variability for most of the traits, not showing a tendency of superiority of a group of clones relative to each other. The groupsof clones of Conilon coffee evaluated in this study showed great potential to be successfully used in breeding programs aiming forproductivity and other characteristics in the south of Espírito Santo.